COVID‐19 and Immunological Dysregulation: Can Autoantibodies be Useful? - Simona Pascolini; Antonio Vannini; Gaia Deleonardi; Michele Ciordinik; Annamaria Sensoli; Ilaria Carletti; Lorenza Veronesi; Chiara Ricci; Alessia Pronesti; Laura Mazzanti; Ana Grondona; Tania Silvestri; et al. (Clinical and Translational Science, 2021)
Coronavirus disease 2019 (COVID‐19) is often associated with interstitial pneumonia. However, there is insufficient knowledge on the presence of autoimmune serological markers in patients with COVID‐19. We analyzed the presence and role of autoantibodies in patients with COVID‐19‐associated pneumonia. We prospectively studied 33 consecutive patients with COVID‐19, 31 (94%) of whom had interstitial pneumonia, and 25 age‐matched and sex‐matched patients with fever and/or pneumonia with etiologies other than COVID‐19 as the pathological control group. All patients were tested for the presence of antinuclear antibodies (ANAs), anti‐antiphospholipid antibodies, and anti‐cytoplasmic neutrophil antibodies (ANCAs). Clinical, biochemical, and radiological parameters were also collected. Fifteen of 33 patients (45%) tested positive for at least one autoantibody, including 11 who tested positive for ANAs (33%), 8 who tested positive for anti‐cardiolipin antibodies (immunoglobulin (Ig)G and/or IgM; 24%), and 3 who tested positive for anti‐β2‐glycoprotein antibodies (IgG and/or IgM; 9%). ANCA reactivity was not detected in any patient. Patients that tested positive for auto‐antibodies had a significantly more severe prognosis than other patients did: 6 of 15 patients (40%) with auto‐antibodies died due to COVID‐19 complications during hospitalization, whereas only 1 of 18 patients (5.5%) who did not have auto‐antibodies died (P = 0.03). Patients with poor prognosis (death due to COVID‐19 complications) had a significantly higher respiratory rate at admission (23 breaths per minute vs. 17 breaths per minute; P = 0.03) and a higher frequency of auto‐antibodies (86% vs. 27%; P = 0.008). In conclusion, auto‐antibodies are frequently detected in patients with COVID‐19 possibly reflecting a pathogenetic role of immune dysregulation. However, given the small number of patients, the association of auto‐antibodies with an unfavorable prognosis requires further multicenter studies.